The Creeping Attachment Induced Technique (CAIT) in Natural and Restored Teeth: Case Reports with 24 Months of Follow-Up - Michele Perelli; Roberto Abundo; Giuseppe Corrente; Paolo Giacomo Arduino (Case Reports in Dentistry)
This article describes a nonsurgical approach for treating gingival recessions and increasing gingival thickness around the natural teeth. Two female patients, presenting gingival recessions at the maxillary frontal teeth, were treated. Patient #1 had a discrepancy among the central maxillary incisors’ gingival margin, and tooth UL1 needed to be restored. Patient #2 presented a buccal gingival recession at tooth UL3. In both cases, the sulcular gingival margin was gently disephitelized with a diamond bur leaving the soft tissue healing by itself. After 4 weeks, the procedure was reperformed. After 6 months, the gingival margins appeared thicker and a creeping attachment was achieved in both cases, obtaining gingival symmetry, related to the adjacent or contralateral teeth, and root coverage. Gingival asymmetry, gingival recessions, and gingival thickness may be improved by means of a guided gentle nonsurgical stimulation, providing creeping attachment in the natural and also restored teeth, with a healthy and stable tissue after 24 months of follow-up.